Universal Health Coverage for Non-communicable Diseases and Health Equity: Reflections on the Role of Ideas and Democratic Decision-Making; Comment on "Universal Health Coverage for Non-Communicable Diseases and Health Equity: Lessons from Australian Primary Healthcare" - Lauren Paremoer (Kerman University of Medical Sciences, 2022)
Fisher et al have published a thought-provoking article exploring the complex relationship between universal health coverage (UHC) and equity. This commentary builds on two of the lessons they highlight: the importance of ideas in determining how exactly UHC advances equity, and the political difficulties of addressing the commercial determinants of health. I argue that equity in UHC can be advanced through interventions that address popular prejudices against public health systems, greater emphasis on structural and commercial drivers of ill-health in health professionals' training, and by ensuring meaningful public participation in decision-making about the institutionalisation and management of UHC. These strategies are important for ensuring that the political, power-laden nature of concepts such as "universality", "health" and "care" are explicitly acknowledged and publicly debated - rather than continuing the current trend of allowing technocrats to reduce UHC to a matter of efficiently and expeditiously financing curative healthcare services.